Hinaus in die Ferne! Lebensreform et randonnée - Claire Milon (Recherches Germaniques)
Hiking spreads across Germany at the end of the 19th century. As a practice rooted both in nature and in the bodies it maintains close relations with the Lebensreform movements. As an outdoor activity, hiking is undeniably a spatialized practice. Since it constitutes a movement of escape from the cities, hiking puts in relation the urban and the outdoor spaces, the latter perceived as “natural spaces” where physical and introspective explorations take place. At the very foundation of hiking, itinerancy supposes the acquisition of spatial and technical skills. Hiking is a movement of the Lebensreform in which a double relationship with space is played out: the activity only makes sense through the territories crossed, but these places are at the same time transformed by the presence of the hikers.